Studi Literatur: Menceritakan Kembali sebagai Metode Penguatan Kemampuan Bahasa Indonesia pada Anak Usia Dini - Simatupang, Nabila Husna; Shahira Afini Azzahra; Fanny Zaskia Ramadhani (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
Improving Indonesian language skills in early childhood is very important to form good communication skills in the future. One effective method to support children's language development is the retelling method. This study aims to examine the application of the retelling method as a strategy to strengthen Indonesian language skills in early childhood, especially in the aspects of speaking and listening. The method used in this research is a literature study with a qualitative descriptive approach. The results showed that the retelling method can improve children's speaking and listening skills and enrich their vocabulary. In addition, this method also deepens children's understanding of the reading text they hear. It is recommended that this method be applied regularly by educators and parents to support Indonesian language development in early childhood.